The analysis of saturated and aromatic mineral oil hydrocarbons in dry foods and from recycled paperboard packages by online HPLC–GC–FID. Issue 12 (2nd December 2018) - Canavar, Öner; Kappenstein, Oliver; Luch, Andreas
ABSTRACT: The purpose of this study was to determine the concentrations of mineral oil hydrocarbons in dry foodstuffs packed in recycled paperboard, which were imported from different foreign countries to Germany. After collection, mineral oil saturated hydrocarbons (MOSH) and mineral oil aromatic hydrocarbons (MOAH) in dry foodstuffs and recycled paperboard were analysed using online coupled high-performance liquid chromatography–gas chromatography–flame ionisation detection (online HPLC–GC–FID) far before the end of the shelf life of the samples. Our results showed that recycled paperboard has MOAH content higher than that of dry foodstuffs. The proportion of MOAH within total mineral oil hydrocarbons was determined to be 7–45% in dry foodstuffs and 4–48% in paperboard. In addition, 29% of the products were found to contain over 1.00 mg/kg MOAH, with a maximum of 2.72 mg/kg in oatmeal. White colour recycled paperboard contained lower amounts of MOSH and MOAH than that of brown and grey colour recycled paperboard. The MOSH concentration in dry foodstuffs ranged from 0.11 to 21.92 mg/kg (˂C25 hydrocarbons), which may be an indication of rapid migration. The lowest determined MOSH concentrations (˂C25 hydrocarbons) were found in sea salt and soda samples, even when their paperboard contained high mineral oil hydrocarbons. Our three samples in packages containing internal bags (for complete barriers) were found to have low mineral oil concentration due to reduced migration through plastic (acrylate-coated polypropylene). However, one sample, a 'crispy' product with an internal bag, contained the extreme amount of 21.92 mg/kg. Differences in contaminants observed in both dry foodstuffs and recycled paperboard may have been due to the different packaging and production techniques of the different countries. In addition, 8 of 24 dry foodstuff samples contained MOSH concentrations frequently exceeding the 2.0 mg/kg limit for MOSH C20 –C35 . Graphical Abstract: